The suppression of tumor necrosis factor-alpha production in response to pathogen stimulation by strenuous exercise and underlying mechanisms - Hiromi Yano; Masataka Uchida; Eri Oyanagi; Noriaki Kawanishi; Daisuke Shiva; Hiromi Kitamura (Japanese Society of Physical Fitness and Sports Medicine, 2012)
In general, physical activity reduces the risk of cancer and infectious diseases. However, strenuous exercise has been shown to transiently increase the risk of infection, and this is referred to as the "open window." Indeed, intense exercise reduces the concentrations of several cytokines in plasma in response to pathogens. The mechanisms responsible for this observation may depend on exercise-induced increased stress hormone secretion, especially that of catecholamines. Exercise-induced catecholamines, acting through β-adrenergic receptors, have been found to be responsible for exercise-induced suppression of plasma tumor necrosis factor-alpha (TNF-α) after lipopolysaccharide (LPS) administration. In the signaling mechanisms of cells, there are no changes in the surface expression of Toll-like receptor (TLR) 4. Although there are also no changes in the LPS-induced TNF-α mRNA expression in tissues after exercise, the TNF-α content in the tissues of exercised animals is lower than that in the tissues of non-exercised animals. Therefore, a strenuous exercise-induced reduction in plasma TNF-α concentration, despite pathogen stimulation, depends on the translation of TNF-α in tissues.